Sosialisasi Thalassemia Kepada Guru Biologi di Banyumas: Upaya Pencegahan Terintegrasi Melalui Kurikulum Sekolah - Lantip Rujito; Diyah Woro Dwi Lestari; Abdul Aziz; Dinar Faiza (Universitas Mathla'ul Anwar Banten, 2018)
THALASSEMIA SOCIALIZATION TO BIOLOGY TEACHERS IN BANYUMAS: EFFORT OF INTEGRATED PREVENTION THROUGH SCHOOL CURRICULUM. Thalassemia is a hematologic disease that causes hemoglobin blood defects. As a result, red blood cells become fragile and unable to perform their standard functions. Thalassemia in Indonesia is a quite lot. Recorded data, the carrier traits are about 3-10%, spread across all provinces. Currently, no final treatment can cure this disease altogether. Regular transfusion and iron chelating drugs are still survival of thalassemia patients. Prevention program is one of efficient handling. The pattern of thalassemia gene decline follows the laws of the recessive Mendel. Prevention is done by campaigning premarital screening to married couples or further to younger individuals so they can plan marriages wisely. High School Biology teachers are an essential factor in preventing thalassemia. They can deliver prevention programs through lessons at school. They can also be pioneers in an early self-detection carrier to teenagers before they plan a marriage. Because of its strategic role, the socialization of thalassemia in high school teachers becomes very important.